ANALISIS CERITA “KITTY DAN KOMPETISI LAMPION” SEBAGAI ALTERNATIF BAHAN AJAR MEMBACA SASTRA DI SD - Fauziyyah, Hilma Mustika; Prana Dwija Iswara (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Literature learning is less interested by elementary school students. One of the reasons is that teaching materials are less attractive to students because they only used textbooks provided by the government. This research aims to describe the children’s story “Kitty dan Kompetisi Lampion” as an alternative literature reading teaching material in elementary school. This research used a qualitative approach with content analysis methods. Data comes from the children’s story book “Kitty dan Kompetisi Lampion” by Paula Harisson. Data was collected through documentation studies. Researchers as a human instrument. The data analysis technique uses data collection, data reduction, and drawing conclusions. The results of the research foound that the children’s story “Kitty dan Kompetisi Lampion” by Paula Harisson has both intrinsic such as theme, storyline, background or setting, characterization, messages, point of view, conflict; and extrinsic story elements consisting of the values of the story and the author’s background. Kitty’s personality structure consists of the id which is realized through the process of imagining and shown through feelings; the ego which is shown in reasoning; and the superego through action, words and advice which reflects society’s moral values. The story “Kitty dan Kompetisi Lampion” is eligibility criteria for teaching materials in terms of language, psychology, and cultural background. The linguistic dimension shows that this book is suitable for high class students. From a psychological dimension, this story book develops character values for its readers which are present in an interesting way. From the cultural background dimension, the culture shown in this book is appropriate with Indonesian culture.